Grasping Glamour - Williams, Megan E. (American Studies, 2013)
This review essay reviews: The Glamour System, by Stephen Gundle and Clino T. Castelli; Glamour: A History, by Stephen Gundle; Glamour in Six Dimensions: Modernism and the Radiance of Form, by Judith Brown; Glamour: Women, History, Feminism, by Carol Dyhouse.